Research progress on mechanized garlic seeding technology in China - Shao, Mingxi; Zhang, Xiumei; Fang, Lizhi; Ma, Guocai; Tian, Jie; Fu, Shenghui (International Journal of Agricultural and Biological Engineering, 2025)
Garlic is a traditional vegetable and an important horticultural crop in China, with its cultivated area and production ranking first among all countries in the world. In recent years, with social and economic development, labor costs have generally risen, which has directly led to the cost of garlic planting rising year after year, the decline in profits from garlic planting, and the continued reduction in garlic planting area. In this review, the development of mechanized planting in the main garlic-producing countries in the world is discussed in detail, and the present situation and characteristics of mechanized planting in China are analyzed. The advanced garlic seeding machinery and existing problems are compared and investigated, and the development status and technical characteristics of garlic seeding mechanization in China are analyzed. On this basis, it is pointed out that China’s garlic sowing mechanization faces the problems of insufficient integration of agricultural machinery and agronomy, lack of unification of planting mode, and imperfection of core functions. In addition, relevant suggestions are put forward for the problems faced by China’s mechanical garlic sowing equipment: develop garlic sowing mechanization equipment according to local conditions, promote standardized garlic planting agronomy, improve the innovation ability of core components, and develop a garlic seeder to meet the agronomic requirements of the country. Key words: garlic; seeding machinery; seeding agronomy; single-seed sowing device; orientation of garlic clove bud DOI: 10.25165/j.ijabe.20251802.9035 Citation: Shao M X, Zhang X M, Fang L Z, Ma G C, Tian J, Fu S H. Research progress on mechanized garlic seeding technology in China. Int J Agric & Biol Eng, 2025; 18(2): 9–20.